A novel press-fit minimally-invasive symphysiodesis technique - Sascha J. Hopp; Antonius Pizanis; Jeremy Briem; Jill Hahner; Laura Mettelsiefen; Steven C. Herath; Tina Histing; Tim Pohlemann; Tobias Fritz (Journal of Experimental Orthopaedics, 2020)
Abstract Objective Instability of the pubic symphysis often results in a poor outcome and reduced mobility of the patient. In some cases, an arthrodesis of the pubic symphysis is required. Until today, there is no data published how many of these procedures are performed annually and there is also no data about the outcome after this extensive surgery. Methods We developed a novel surgical technique to address the arthrodesis of the pubic symphysis in a minimally invasive approach. Therefore, we used for this purpose modified instruments and performed the transplantation of a cylindrical bone substitute into the pubic symphysis, without an extensive approach or dissecting the anterior or posterior symphyseal ligaments. Results Using this novel technique, a minimally invasive symphysiodesis was achieved in radiological findings, after the procedure. Conclusion Thus, this actually minimally invasive surgical technique seems to be a promising advancement for the arthrodesis of the pubic symphysis.